PENGEMASAN PAKET WISATA CITY TOUR BERBASIS BUDAYA DI KOTA DENPASAR BALI - Ary Mahendra Putra, I Wayan; Kusuma Negara, I Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 1 (2016): Jurnal IPTA (July 2016), 2016)
Denpasar city has a variety of tourist potential, namely the potential of cultural tourism such as historical buildings, art attractions, a traditional market with a wide variety of traditional dishes as well as community activities related to culture. Given these potentials can be developed into a tourist city tour packages in Denpasar. In connection with the travel package packing city tour, then the formulation of issues to be discussed are (1) What is the potential of the city of Denpasar as a cultural tourist attraction ?, (2) How packaging travel packages culture-based city tour in Denpasar? This study aims to determine the potential of the city of Denpasar as cultural charms, knowing the way of packaging travel packages culture-based city tour in the city of Denpasar. Data collection techniques in this study was done by observation, interview, and literature study. The results of this study indicate that the city of Denpasar has tourism potential which comprise the majority of the potential of cultural tourism, the potential that made travel packages in this study is the charm of the castle and temple, traditional market and museum in the city of Denpasar The potential is then packaged in three forms, namely, in narrative form, tabular and graphical form four- travel packages including: Melali ke Puri, Heritage Denpasar City Tour, Beautiful Cultural of Denpasar City Tour, Historic Denpasar City Tour.
Keywords: Potency, Cultural Tour, Tour Package